Legal Analysis Of Embezzlement Of Rental Four Wheeled Motor Vehicles In Criminal Law Perspective - MUhammad Nasir Sitompul (International Asia Of Law and Money Laundering (IAML), 2023)
This study aims to explain the factors that cause the crime of embezzlement of rental four-wheeled motor vehicles, obstacles in overcoming it and the efforts made by law enforcement in combating crime of rental four-wheeled motor vehicles. The Data obtained in the writing of this article was done with literature and Field Research. Literature research was conducted to obtain secondary data by studying laws and books, while Field Research was conducted to obtain primary data by studying, reviewing cases and interviewing respondents and informants. From the results of the study, it is known that the cause of the crime of embezzlement of rental four-wheeled motor vehicles is due to economic factors, factors of Community Legal Awareness, utilization of opportunities, not using a driver or Key Release System, and weak security system factors. Obstacles in overcoming the factor of facilities and infrastructure, people who are apathetic in helping the police, the difficulty of presenting witnesses who know the incident the perpetrator or defendant in getting the goods, and the car that was embezzled has been mortgaged to a third party. The efforts made are to carry out raids or patrols carried out in a directed and regular manner against motor vehicles and their letters to ensure that the vehicle is not a vehicle obtained from the results of criminal acts, especially theft and embezzlement. It is recommended to every car rental service owner to not only supervise, but also to improve the security system so that there is no more embezzlement of rental cars and law enforcement must be more active in making efforts both preventive and repressive efforts in the case of criminal acts of embezzlement of rental four-wheeled motor vehicles.